Structure and mechanisms of protein phosphatases - Barford, David (Henry Stewart Talks, 2010)
Reversible protein phosphorylation, Classification of protein phosphatases, Protein tyrosine phosphatase family, structure of PTP1B, catalytic mechanism, basis for pTyr specificity, recognition of IRK, regulation by ROS and cyclic sulphenamide, Dual specificity phosphatases, Eya protein tyrosine phosphatases, PPP family of Ser/Thr phosphatases, structure of PP1, catalytic mechanism, inhibition by okadaic acid and microcystin, targeting subunits, PP2A, PP2B, PP5, PPM family of Ser/Thr phosphatases, structure, catalytic mechanism, Summary